MINIMIZATION OF THE EXECUTIVE ENGINE OF THE RESONANT ELECTRIC STEERING DRIVE. - Бондарчук, П. С. (Science-based technologies, 2014)
The resonant electric steering drive (RESD) can be applied as a part of control systems of all classes of rotating roll missiles. Existing samples RESD still are far from perfect also their mass-dimensional characteristics are superfluous. Spent earlier quantitative estimation of excess of weight existing RESD showed that the power and weight of the executive engine (EE) the best known sample are exceeded now more than in 10 times. The given work is spent for the purpose of definition of limits of minimization of weight of the EE and power consumption RESD. In the given work the problem of achievement of the best weight and dimensions and power characteristics of the steering drive by minimization EE dares. Minimization EE is spent on the basis of the data about energy of losses and superheat temperature of windings EE of the existing drive. The weight of copper of wires of windings hypothetical minimized EE has been reduced to such level that excessive heating of windings from energy of losses was close to an allowance 120 °С. In relation to the existing engine the weight and volume are reduced in 64 times, the minimized EE has diameter of 6 mm and length of 9 mm, weight about 1 g. Check of achievable level of minimization EE is spent. Check is spent by a method of modeling of the drive with hypothetical minimized EE at the solution of a typical task of flight control of the hypothetical rocket. Results of modeling showed that the weight and volume minimized EE are close to extreme achievable level. The estimation of an achievable technical level of the hypothetical minimized drive showed that it matches to level of the best existing sample of the electric steering drive.